RSIS-WTO Parliamentary Workshop – US Blacklist on Huawei : Leverage for the US-China Trade Talks? - Lyu, Mengting (2019)
The United States added Huawei Technologies Co. Ltd. to the US Entity List of threats to the US telecommunications industry. Google and other US companies suspended some businesses with Huawei after the blacklisting. Trump seems to use the blacklisting as leverage in the US-China trade negotiations, which does not bode well for a successful deal.